Liquid Soap Formulation from Virgin Coconut Oil (VCO) With the Addition of Butterfly Pea (Clitoria ternatea L) Extract - Wati Setyaningrum; Wisnu Broto (Waste Technology, 2023)
In Indonesia, several types of soap have started to spread evenly. One type of soap that is popularly used by Indonesian people is liquid soap. In the manufacture of liquid soap requires the same main raw materials, namely oil/fat and KOH alkaline base. One of the most frequently used oils/fats is virgin coconut oil (VCO). In addition, to increase the usefulness of soap, active ingredients are also needed. Natural/plant active ingredients such as butterfly pea flowers are a solution to reducing the use of chemical active ingredients. This butterfly pea plant has several good ingredients for skin health. Therefore, the manufacture of liquid soap with butterfly pea flower extract was carried out. This study used a factorial design method to determine the optimal liquid soap formulation. With several independent variables used, including KOH concentration, VCO concentration and the length of time of stirring, the results of soap that met SNI were obtained from testing for pH, viscosity, free alkali content, density and water content. The optimal formulation for making butterfly pea flower extract liquid soap is at a concentration of 20% KOH, with a concentration of 50% VCO and a stirring time of 45 minutes.